Transformation of GP Ansor's Cadre Education Management Strategy and Digital Preaching in the Era of Information Disruption - Khamdan Asyfahaani; Fauzi Fauzi; Fajar Hardoyono; Slamet Pamuji (JUMPA : Jurnal Manajemen Pendidikan, 2025)
Transformation of GP Anshor's Cadre Education MThe rapid expansion of digital technology has reshaped the communication landscape of religious organizations, requiring adaptive strategies in both da’wah practices and cadre education management. This study examines how GP Ansor, an Islamic youth organization in Indonesia, integrates digital media into its organizational practices in response to the dynamics of the information disruption era. Using a qualitative case study approach, data were collected through in-depth interviews, documentation analysis, and digital observation of social media platforms, including Instagram, YouTube, and Twitter/X. The findings reveal that GP Ansor has developed a multifaceted digital da’wah strategy by optimizing social media, establishing counter-narratives against radicalism through structured cyber initiatives, and implementing digital literacy programs as part of its cadre development process. Furthermore, digital learning practices have expanded beyond formal training into interactive and participatory online spaces, allowing cadres to actively engage in content production and public discourse. However, the study also identifies several challenges, including disparities in digital competencies among cadres, limitations in technological infrastructure, and the lack of systematic evaluation mechanisms. These findings highlight that digital transformation within religious organizations is not merely a technological shift but involves a reconfiguration of learning processes, organizational structures, and human resource development. The study contributes to the field of Islamic education management by offering insights into how digital-based cadre education can be designed to remain adaptive, sustainable, and aligned with the promotion of religious moderation in contemporary digital environments.anagement Strategy